SOSIALISASI PENTINGNYA PENGETAHUAN DASAR AKUNTANSI PADA PELAKU UMKM DI DESA SADE LOMBOK TENGAH - Pratiwi, Widya; Nuada, I Wayan; Syukri, Muhammad; Rizkina, Rusdayanti; Aini, Khotiatul; Rizal, Lalu (LPPM Institut Pendidikan Nusantara Global, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in improving the Indonesian economy. However, MSMEs often face problems due to unorganized financial management. This is due to the lack of knowledge of MSME actors regarding Accounting Science. As a result, MSME actors have difficulty applying accounting practices in managing their business. Seeing this problem, it is necessary to conduct socialization for MSME actors in Sade Village. This socialization aims to increase the knowledge of MSME actors about the importance of basic accounting knowledge in the development of MSMEs. The stages of this service activity include the preparation stage, implementation stage, and evaluation. After the socialization, the knowledge and insight of MSME actors on the importance of basic accounting knowledge in the development of MSMEs increased. Likewise, the awareness of MSME actors to apply accounting practices in business financial management has also increased. This service activity has a positive impact on increasing the knowledge and insight of MSME actors because the use of accounting for MSMEs is very important to help business owners or business actors run their businesses.